2021
DOI: 10.1016/j.cels.2021.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Human plasma IgG1 repertoires are simple, unique, and dynamic

Abstract: Highlights d Novel LC-MS-based methods enable personalized IgG1 profiling in plasma d Each donor exhibits a simple but unique serological IgG1 repertoire d This repertoire adapts to changes in physiology, e.g., sepsis d Individual plasma IgG1 clones can be identified by combining top-down and bottom-up proteomics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(116 citation statements)
references
References 56 publications
10
96
0
Order By: Relevance
“…Stringent analysis revealed that about 7-10% of these distinct ion signals matched to a Thr 109 ‘missed cleavage’, thus leaving still ~400 unique clones. Thus, as earlier observed for IgG1 in plasma ( 14 ), we found that in human milk a limited number of clones dominate the sIgA1 repertoire.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Stringent analysis revealed that about 7-10% of these distinct ion signals matched to a Thr 109 ‘missed cleavage’, thus leaving still ~400 unique clones. Thus, as earlier observed for IgG1 in plasma ( 14 ), we found that in human milk a limited number of clones dominate the sIgA1 repertoire.…”
Section: Resultssupporting
confidence: 87%
“…This approach indeed provides antibody sequences, but these are likely not identical to the fully matured protein sequence of the Igs that are finally produced and secreted (31). We largely overcome these limitations by analyzing the Ig profiles of human biofluids directly, which we demonstrate here for sIgA1 from human milk and plasma, and have previously shown for IgG1 from human plasma (14).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations